CD150 and CD180 are involved in regulation of transcription factors expression in chronic lymphocytic leukemia cells - Gordiienko, I.M.; Shlapatska, L.M.; Kholodniuk, V.M.; Kovalevska, L.M.; Ivanivskaya, T.S.; Sidorenko, S.P. (Experimental Oncology, 2017)
Background: Sequential stages of B-cell development is stringently coordinated by transcription factors (TFs) network that include B-lineage commitment TFs (Ikaros, Runx1/Cbfb, E2A, and FOXO1), B-lineage maintenance TFs (EBF1 and PAX5) and stage specific set of TFs (IRF4, IRF8, BCL6, BLIMP1). Deregulation of TFs expression and activity is often occurs in malignant B cells. The aim of this study was to evaluate TFs expression in chronic lymphocytic leukemia cells taking into consideration CD150 cell surface expression. From other side we attempted to regulate TFs expression via CD150 and CD180 cell surface receptors. Materials and Methods: Studies were performed on normal peripheral blood B-cell subpopulations and chronic lymphocytic leukemia (CLL) cells isolated from peripheral blood of 67 primary untreated patients with CLL. Evaluation of TFs expression was performed on mRNA level using qRT-PCR and on protein level by western blot analysis. Results: Median of PAX5 and EBF1 mRNA expression was higher in cell surface CD150 positive (csCD150⁺) compared to csCD150⁻ CLL cases or normal CD19⁺ and CD19⁺CD5⁺ B-cell subsets. Differences in mRNA expression of IRF8, IRF4 and BLIMP1 between studied groups of CLL and normal B cells were not revealed. All CLL cases were characterized by downregulated expression of PU.1 and BCL6 mRNAs in comparison to normal B cells. At the same time elevated SPIB mRNA expression level was restricted to CLL cells. Protein expression of IRF4, IRF8 and BCL6 was uniformly distributed between csCD150⁻ and csCD150⁺ CLL cases. PU.1 protein and CD20 that is direct PU.1 target gene positively correlated with CD150 cell surface expression on CLL cells. Ligation of CD150 and CD180 alone or in combination upregulated IRF8 and PU.1 while downregulated the IRF4 mRNA expression. Signaling via CD150 or CD180 alone elevated the level of BCL6 mRNA. Strong downregulation of IRF4 mRNA was observed after CD150, CD180 or CD150 and CD180 coligation on CLL cells. We found that in CLL cells CD150 is a negative regulator of SPIB while CD180 is involved in upregulation of EBF1 expression level. Moreover, CD180 ligation on CLL cells caused increase of CD150 mRNA level that is a one of the EBF1 target genes. Conclusions: Analysis of TFs expression profile revealed upregulated SPIB mRNA level and downregulated PU.1 in CLL cells. CD150 and CD180 receptors may modulate transcriptional program in CLL cells by regulating the TFs expression levels